Pengaruh Permintaan Akhir dan Barga terhadap ImporTotal Indonesia: Analisis Cointegration dan Error Correction Model - Mutmainah, Isbandriyati (Jurnal Ekonomi dan Pembangunan Indonesia, 2009)
This research is aimed to investigate the influence of final demand and price to Indonesian agregate imports in the long-run and short-run. We use analytical technique cointegration test Johansen procedures for the long-term influence, and Error Correction Model to estimate the short-term influence, by using quarterly time series data period from 1980 to 2004. From the result of cointegration test and Error Correction Model we found that in the long-term, all of final demand components and price except private investment are important in determining Indonesian agregate imports. The government expenditure variable has the highest influence, while in the short-term all of independent variables except private consumption are important in determining Indonesian agregate imports and foreign price variable has the highest influence.